Novel Nile Blue derivatives as ﬂuorescent probes for DNA - Raju, B. Rama (2013)
Cationic dyes based on benzo[a]phenoxazinium chlorides either mono- or disubstituted with ethyl, octyl and dodecyl groups at the amino side chain at the 9-position of the tetracyclic ring, and possessing a propyl group at the 5-amino position were synthesised, characterised and used in photophysical studies with DNA and in agarose gel electrophoresis assays. Photophysical results showed that compounds with diethyl and octyl substituents intercalated DNA above a phosphate dye ratio of 10. All compounds associated with DNA as evidenced by their use as colored markers of migrating DNA bands in agarose gel electrophoresis experiments.